Sleepless city [large type] - Coleman, Reed Farrel, 1956- (Coleman, Reed Farrel, 1956- Nick Ryan series., 2023)
Nick Ryan is the mayor's private cop, the fixer, with conflicted loyalties and a divided soul. But what happens when the man who knows all the city's secrets becomes a threat to both sides of the law?